International Strategic Management - Pham, Phuong Mai (Khoa Quốc tế, ĐHQGHN, 2020)
The aims of this module include two main points: (1) to provide students a sound background on the international business environment, opportunities and challenges to management in this global market; (2) to provide students knowledge and skills to manage business effectively in the international market.